2022
DOI: 10.3390/vaccines10122002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 IgG Antibodies Post-COVID-19 or Post-Vaccination in Libyan Population: Comparison of Four Vaccines

Abstract: Measurement of strength and durability of SARS-COV-2 antibody response is important to understand the waning dynamics of immune response to both vaccines and infection. The study aimed to evaluate the level of IgG antibodies against SARS-CoV-2 and their persistence in recovered, naïve, and vaccinated individuals. We investigated anti-spike RBD IgG antibody responses in 10,000 individuals, both following infection with SARS-CoV-2 and immunization with SARS-COV-2 AstraZeneca, Sputnik V, Sinopharm, and Sinovac. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…The total number of infected individuals in the NCDC registry was 341091 on 30 th September 2021. Our results thus confirm the findings of previous studies on the protective effect of full vaccination as single dose vaccine immunity tends to wane faster and may not mount a good immune response after infection except in previously infected individuals (4). We also found no difference in in mortality between unvaccinated and partially vaccinated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The total number of infected individuals in the NCDC registry was 341091 on 30 th September 2021. Our results thus confirm the findings of previous studies on the protective effect of full vaccination as single dose vaccine immunity tends to wane faster and may not mount a good immune response after infection except in previously infected individuals (4). We also found no difference in in mortality between unvaccinated and partially vaccinated.…”
Section: Discussionsupporting
confidence: 90%
“…COVID-19 vaccinations have been approved for emergency use worldwide (3). The humoral immune responses elicited by four vaccines used in Libya were previously evaluated in the general population (4). This study showed that Sputnik V and AstraZeneca vaccines developed a robust antibody response especially in previously infected individuals higher than Sinovac and Sinopharm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous infection with COVID-19 has previously been shown to cause robust and high levels of anti-SARS-CoV-2 antibodies in vaccinated individuals compared with unvaccinated people, but these antibodies decline rapidly over time. [47][48][49] Vaccination-induced antibodies may not generate sufficient immune memory; therefore, repeated booster vaccinations at regular intervals appear necessary. Further studies are needed to understand the dynamics of immune response decline to vaccines and infections.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar published observations were also made by our team at the Libyan Biotechnology Research Center. 5 Individuals younger than 50 years exhibited higher antibody titers compared to those older than 50 years. A study by Wolszczak et al demonstrated a significant agerelated difference in antibody levels among individuals who had received one dose of the COVID-19 vaccine.…”
Section: Comparison Of Total Anti-sars-cov-2 Antibody Levels In Vacci...mentioning
confidence: 95%